The diagnosis and treatment of acute spinal cord injury - Cryns, Nora; Himmelhaus, Sandra; Irrgang, Sophie; Ernst, Moritz; Weidner, Norbert; Scheel-Sailer, Anke (Deutsches Ärzteblatt, 2025)
Background: In Germany, the incidence of traumatic spinal cord injury is approximately 16 per million inhabitants per year. This article aims to present evidence-based diagnostic and therapeutic measures for the first 14 days after injury to minimize neural damage, prevent complications, and preserve functioning as much as possible. - Methods: After the formulation of key questions, systematic literature searches were carried out on multiple topics. The findings were evaluated for methodological quality, and recommendations were agreed upon by consensus. - Results: Spinal cord injury may be due to traumatic (e.g., a fall) or non-traumatic causes (e.g., ischemia). The evidence presented here on the diagnosis and treatment of spinal cord injury is mainly based on observational studies. 15 evidence-based and 43 consensus-based recommendations were formulated. The patients’ neurological course should be monitored by clinical neurological examination according to the International Standards for Neurological Classification of Spinal Cord Injury (strength of recommendation [SOR]: strong). If traumatic spinal cord injury is suspected, the patient should be transported as rapidly as possible to a tertiary-care trauma center (SOR: strong). Spine decompression surgery should be performed within 24 hours (SOR: weak). Corticosteroids should not be given in the acute phase of traumatic spinal cord injury (SOR: strong) but are indicated if the spinal cord is compressed by a tumor (SOR: strong). The mean arterial pressure should be between 70 and 90 mmHg for the first 2–3 (maximum 7) days (SOR: weak). Pharmacotherapy with heparin should be started early to prevent thromboembolism, with due attention to the risk of hemorrhagic complications (SOR: strong). - Conclusion: This (S3 level) clinical practice guideline aims to standardize clinical care. Early interdisciplinary management is essential to protect at-risk neural tissue and to prevent complications, and constitutes a key prerequisite for long term neurological and functional recovery. No neuroprotective or neuroregenerative treatments are available to date.
Gesehen am 24.11.2025